Low prevalence of CHEK2 gene mutations in multiethnic cohorts of breast cancer patients in Malaysia. - Suriati Mohamad; Nurismah Md Isa; Rohaizak Muhammad; Nor Aina Emran; Nor Mayah Kitan; Peter Kang; In Nee Kang; Nur Aishah Mohd Taib; Soo Hwang Teo; Sharifah Noor Akmal (PLoS ONE, 2015)
CHEK2 is a protein kinase that is involved in cell-cycle checkpoint control after DNA damage. Germline mutations in CHEK2 gene have been associated with increase in breast cancer risk. The aim of this study is to identify the CHEK2 gene germline mutations among high-risk breast cancer patients and its contribution to the multiethnic population in Malaysia. We screened the entire coding region of CHEK2 gene on 59 high-risk breast cancer patients who tested negative for BRCA1/2 germline mutations from UKM Medical Centre (UKMMC), Hospital Kuala Lumpur (HKL) and Hospital Putrajaya (HPJ). Sequence variants identified were screened further in case-control cohorts consisting of 878 unselected invasive breast cancer patients (180 Malays, 526 Chinese and 172 Indian) and 270 healthy individuals (90 Malays, 90 Chinese and 90 Indian). By screening the entire coding region of the CHEK2 gene, two missense mutations, c.480A>G (p.I160M) and c.538C>T (p.R180C) were identified in two unrelated patients (3.4%). Further screening of these missense mutations on the case-control cohorts unveiled the variant p.I160M in 2/172 (1.1%) Indian cases and 1/90 (1.1%) Indian control, variant p.R180C in 2/526 (0.38%) Chinese cases and 0/90 Chinese control, and in 2/180 (1.1%) of Malay cases and 1/90 (1.1%) of Malay control. The results of this study suggest that CHEK2 mutations are rare among high-risk breast cancer patients and may play a minor contributing role in breast carcinogenesis among Malaysian population.